2019
DOI: 10.1080/19476337.2019.1624622
|View full text |Cite
|
Sign up to set email alerts
|

High pressure extraction increases the antioxidant potential and in vitro bio-accessibility of bioactive compounds from discarded blueberries

Abstract: Unlike conventional extraction (CE) methods, high hydrostatic pressure extraction (HHPE) uses less solvent volume and reduced extraction times. We show here that HHPE increases extractability, antioxidant capacity and bio-accessibility of the bioactive compounds from discarded blueberries when compared to CE. Bioactive compounds were extracted by CE with agitation and by HHPE at 500 MPa for 5, 10 and 15 min. The highest content of anthocyanins (117.08mg 100g −1 FW), polyphenols (9.56mg 100g −1 FW), flavonoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 60 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Briones-Labarca et al [ 87 ] demonstrated that the application of HHPE to extract the bioactive compound from discarded blueberries increased the content of anthocyanins, polyphenols, and flavonoids, as well as the antioxidant capacity by DPPH and FRAP compared with conventional extraction. However, although the bio-accessibility of the polyphenols and flavonoids also increased with HHPE vs CE, the anthocyanins showed a decrease in the bio-accessibility after HHPE.…”
Section: Extraction Methods Used To Extract Anthocyaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briones-Labarca et al [ 87 ] demonstrated that the application of HHPE to extract the bioactive compound from discarded blueberries increased the content of anthocyanins, polyphenols, and flavonoids, as well as the antioxidant capacity by DPPH and FRAP compared with conventional extraction. However, although the bio-accessibility of the polyphenols and flavonoids also increased with HHPE vs CE, the anthocyanins showed a decrease in the bio-accessibility after HHPE.…”
Section: Extraction Methods Used To Extract Anthocyaninsmentioning
confidence: 99%
“…However, although the bio-accessibility of the polyphenols and flavonoids also increased with HHPE vs CE, the anthocyanins showed a decrease in the bio-accessibility after HHPE. In addition, they proved that the anthocyanins extracted increased from 15.1 to 39.4% with the time of the extraction from 5 to 15 min when compared to CE [ 87 ].…”
Section: Extraction Methods Used To Extract Anthocyaninsmentioning
confidence: 99%
“…According to Patras et al [ 53 ], high pressure application could be responsible for phenolic compound degradation in some fruits. This effect is a consequence of peroxidase and polyphenol oxidase activity that oxidize phenolic quinones [ 54 ]. de Jesus et al [ 55 ] evaluated the effect of three different pressures (400, 500, and 600 MPa) on microbial inactivation and anthocyanin extraction from açaí pulp, and observed that high hydrostatic pressure was not able to completely inactivate peroxidase and polyphenol oxidase from açaí pulp.…”
Section: Resultsmentioning
confidence: 99%
“…Anthocyanin extraction was positively influenced by HHE time. The increase in application time (5 min to 15 min) increased analyte extraction due to equilibrium of pressure between the inside and outside of the material or the higher diffusion speed of the solvent when shorter times were applied on HHE [ 54 ]. This trend was observed by Briones-Labarca et al [ 57 ] that studied HHE of Chilean papaya seeds using 500 MPa and different extraction times (5, 10, and 15 min).…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenolic and antioxidant extracts resulting from this technique present better antioxidant activity and, when studied in in vitro analysis, they present good bioaccessibility and decrease the viability of cancer cells [ 10 , 41 ]. However, due to the type of equipment used, there are few studies that exist regarding the application of this technique with the spices that this review covered.…”
Section: Environmentally Friendly Techniques In the Extraction Of mentioning
confidence: 99%